Portugal : Sixth Post-Program Monitoring Discussions-Press Release; Staff Report. (IMF Staff Country Reports; Country Report ;, 2018)
This paper presents an overview of the Sixth Post-Program Monitoring Discussions with Portugal. The Portuguese economy has strengthened. Supported by a benign external environment, job-rich growth has gathered momentum since late 2016. The headline fiscal balance continued to benefit from stronger growth, controlled budget execution, and falling interest costs, with the 2017 deficit target of 1.4 percent of GDP likely to have been met with some margin. Financial stability has also improved with various bank capital augmentations and the sale of Novo Banco in 2017. Growth is projected at 2.2 percent in 2018. Downside risks in the near term are mostly external in nature and appear moderate.